Edukasi Jajanan Sehat untuk Menjaga Kesehatan Ginjal pada Anak Sekolah Dasar - Titis Wening Setyoharsih; Esti Nur Janah; Siti Fatimah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The kidneys are vital organs responsible for maintaining fluid and electrolyte balance, filtering waste products, and supporting overall body homeostasis. Therefore, maintaining kidney health from an early age is essential to prevent the development of kidney-related diseases later in life. Elementary school children often consume snacks and beverages that are high in sugar, salt, artificial coloring, and flavoring, which may negatively affect kidney health if consumed excessively over a long period. One effective preventive strategy is to provide health education through school-based awareness programs. This educational activity was conducted for fourth- to sixth-grade students at Muhammadiyah Elementary School Bumiayu using an interactive learning approach supported by animated videos and PowerPoint presentations. The use of engaging visual media successfully increased students' enthusiasm, participation, and motivation throughout the learning process. The results demonstrated an improvement in students' knowledge of kidney health, as evidenced by their ability to answer questions correctly during the recall and feedback sessions through a simple quiz. These findings indicate that interactive health education is an effective approach to improving children's understanding of kidney health and promoting healthy lifestyle habits from an early age.